Try NerdPal! Our new app on iOS and Android

Simplify the expression $\frac{x^3+x-1}{x^4+6x^2+9}$

Step-by-step Solution

Go!
Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Final Answer

$\frac{x^3+x-1}{\left(x^{2}+3\right)^{2}}$
Got another answer? Verify it here

Step-by-step Solution

Problem to solve:

$\frac{x^3+x-1}{x^4+6x^2+9}$

Choose the solving method

1

The trinomial $x^4+6x^2+9$ is a perfect square trinomial, because it's discriminant is equal to zero

$\Delta=b^2-4ac=6^2-4\left(1\right)\left(9\right) = 0$

Learn how to solve polynomial long division problems step by step online.

$\Delta=b^2-4ac=6^2-4\left(1\right)\left(9\right) = 0$

Unlock this full step-by-step solution!

Learn how to solve polynomial long division problems step by step online. Simplify the expression (x^3+x-1)/(x^4+6x^2+9). The trinomial x^4+6x^2+9 is a perfect square trinomial, because it's discriminant is equal to zero. Using the perfect square trinomial formula. Factoring the perfect square trinomial.

Final Answer

$\frac{x^3+x-1}{\left(x^{2}+3\right)^{2}}$
SnapXam A2
Answer Assistant

beta
Got another answer? Verify it!

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Tips on how to improve your answer:

$\frac{x^3+x-1}{x^4+6x^2+9}$

Time to solve it:

~ 0.05 s